Analysis Pregnancy Exercise And Type of Childbirth In RSIA Mutiara Bunda Malang - Hidajaturrokhmah, Nur Yeny; Rohmah, Rizalatul (STRADA : Jurnal Ilmiah Kesehatan, 2019)
This study uses simple random sampling technique with the independent variable is pregnancy exercise and the dependent variable is types of childbirth. Data collection by using notes of pregnancy exercise attendance and medical record of nursing respondents. The results of the research show that from 23 respondents, 12 (52%) respondents who participated in pregnancy exercise routinely experienced vaginal childbirth. Whereas, 11 (48%) respondents who did not routinely participate in pregnancy exercises experienced childbirth by sectio caesarea. Based on Chi square statistical test results are obtained p = 0,000 (p = < 0,05) so reject H0, which means that there is relationship between pregnancy exercise and the type of childbirth in RSIA RSIA Mutiara Bunda Malang. The results of this study indicate that doing pregnancy exercise routinely is strongly related to the type of Childbirth